Spiritual experience of an elder in oncological preoperative care: case report - Silva, Arthur Fernandes da; Brasil, Aline Quental; Freire, Juliana Fontes; Oliveira, Ana Carolina Duarte de; Ferreira, Alberto Gorayeb de Carvalho; Lopes, José Maurício Pereira; Bandeira, Suziy de Matos (Revista de Medicina, 2016)
Attention to the spiritual dimension is critical to understanding cancer patients as integral beings. Spiritual assessment can identify spiritual needs as purpose, faith and relationships in life to be addressed through specific guidelines. New studies have shown the high prevalence of spiritual experiences in subjects noncarriers of psychotic or dissociative disorders, usually in clinical and institutionalized samples. Such awareness changes have personal and communitarian value. Case report: M.A.C., 88 years old, man, widowed and living in Mauriti-CE, admitted in April 2015 at an oncologic ward. On admission, he showed intense desire to undergo surgery, despite the high cardiovascular and postoperative risks. When argued about comfort sources, he pointed out that his belief in God sustained him and reported a spiritual experience that took place the night before the admission: during sleep, he was alone in his room, when it is lit and three figures presented; the patient identified them as “Our Lady accompanied by two children,” and their presence relieved his anxiety and fear of surgery. Touched, he reported to believe that the same would accompany him during the procedure and alleviate his suffering. During his hospitalization the patient presented himself calm, oriented, without consciousness alterations, confusional state, hyperactivity or underactivity or positive symptoms. Clinical and laboratory tests did not suggest psychopathological or organic causes that could justify the reported experience, strengthening thus its vision as a spiritual experience. CONCLUSION: to provide comprehensive care to patients is to understand their experiences and goals and support their coping resources. Additional studies should deepen interventions to better access and watch these spiritual experiences, clarifying their non-pathological nature.